2022
DOI: 10.1182/blood.2021013733
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of CD19-specific CAR T cell–based therapy in B-cell acute lymphoblastic leukemia patients with CNSL

Abstract: Few studies have described chimeric antigen receptor (CAR) T-cell therapy for B-cell acute lymphoblastic leukemia (B-ALL) patients with central nervous system leukemia (CNSL) due to concerns for poor response and treatment-related neurotoxicity. Our study included 48 relapsed/refractory B-ALL (R/R B-ALL) patients with CNSL to evaluate the efficacy and safety of CD19-specific CAR T-cell-based therapy. The infusion resulted in overall response rate of 87.5% (95% confidence interval [CI], 75.3-94.1) in bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 33 publications
0
44
0
1
Order By: Relevance
“…Recently, Qi et al. ( 31 ) found that CD19-specific chimeric antigen receptor T-cell-based therapy might provide a potential treatment option for B-cell ALL patients with CNSL. Alternately, Tang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Qi et al. ( 31 ) found that CD19-specific chimeric antigen receptor T-cell-based therapy might provide a potential treatment option for B-cell ALL patients with CNSL. Alternately, Tang et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that intrathecal chemotherapy is much more likely to cause catastrophic consequences (28)(29)(30). Recently, Qi et al (31) found that CD19-specific chimeric antigen receptor T-cell-based therapy might provide a potential treatment option for B-cell ALL patients with CNSL. Alternately, Tang et al reported results from the CCCGALL-2015 trial, where they found that upfront dexamethasone might reduce leukemic blasts in the blood and CNS before diagnostic lumbar puncture and general anesthesia might reduce the risk of TLP, while CSF flow cytometry might allow a more accurate diagnosis (32).…”
mentioning
confidence: 99%
“…CAR-T cells lacking CXCR4 exhibit poor migration and retention in the bone marrow, let alone trafficking into the CNS with its physical barrier, the blood-brain barrier (BBB). However, recent clinical trials proved the safety and efficacy of CD19 CAR-T cell therapy with a high response rate in patients with CNS leukemia and lymphoma (Siddiqi et al, 2021;Tan et al, 2021;Qi et al, 2022). This suggests that there may be other possible mechanisms for the CNS infiltration of CAR-T cells.…”
Section: Chemotaxismentioning
confidence: 99%
“…To our knowledge, Xu et al [52] have conducted the largest clinical trial to date exploring the efficacy and safety of CD19 CAR-T-cell therapy for R/R B-cell acute lymphoblastic leukemia (ALL) with CNS invasion. Severe CRS (grade ≥3) and ICANS (grade ≥3) were observed in 9 (18.8%) and 11 patients (22.9%), respectively.…”
Section: Clinical Data On Cd19 Car-t Therapy For Cnslmentioning
confidence: 99%